PENGAPLIKASIAN MEDIA GAME ONLINE “BERLAYAR MENCARI HARTA KARUN” KEPADA KENAIKAN PENGETAHUAN SAYUR DAN BUAH PADA ANAK MUDA USIA 15-21 TAHUN - Danisa Alifa Salsabila; Ratih Kurniasari (Amerta Nutrition, 2022)
Background: Consumption of vegetables and fruit for young people in Indonesia is still far from the sufficient category (<400g/day). One of the contributing factors is the low knowledge of balanced nutrition, especially in the guidelines that recommend consuming vegetables and fruit per day. Online game media is used as an effort to increase young people's knowledge of vegetables and fruits because they prefer technology-based games. Objectives: Measuring the influence of the application of the online game "Berlayar Mencari Harta Karun" to the increase in knowledge of vegetables and fruits in young people aged 15-21 years. Methods: This study uses quantitative research, a pre-experimental type with one group pre-posttest design. Subjects as many as 20 people using the inclusion criteria that have been determined by the researcher. The instruments used are knowledge questionnaires and online game media "Berlayar Mencari Harta Karun" which can be accessed through each respondent's cellphone. Data analysis performed with paired T-Test and Wilcoxon test with a significance level of 0.05. Results: The results of the paired T-Test and the Wilcoxon test showed a significant difference in the value of knowledge about vegetables and fruit (p = 0.000) seen from initial nutritional knowledge and after being given the online game media "Berlayar Mencari Harta Karun." Conclusions: The application of educational media using the online game "Berlayar Mencari Harta Karun" succeeded in significantly increasing nutritional knowledge about vegetables and fruits.